2023
DOI: 10.1002/chem.202300818
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a Strictly T‐Shaped Phosphine Ligated by an Acridane Derived NNN Pincer Ligand

Abstract: The steric tuning of a tridentate acridane-derived NNN pincer ligand allows for the isolation of a strictly Tshaped phosphine that exhibits ambiphilic reactivity. Welldefined phosphorus-centered reactivity towards nucleophiles and electrophiles is reported, contrasting with prior reports on this class of compounds. Reactions towards oxidants are also described. The latter result in the two-electron oxidation of the phosphorus atom from + III to + V and are accom-panied by a strong geometric distortion of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 96 publications
3
16
0
Order By: Relevance
“…Two-electron oxidation of the P-center in 1 by reaction with an equimolar amount of p-anisylazide (4-methoxyphenylazide) also proceeded smoothly upon heating at 90 °C for several hours, cleanly forming iminophosphorane 5. This species was characterized by a 31 P NMR chemical shift of 1.8 ppm, comparable to the previously reported iminophosphoranes of PN3 (at 14.5 ppm) [39] and PN3 acr (at 18.1 ppm), [28] although it must be noted that the specific reaction conditions (temperature required and aryl azide used) distinctly vary between these three systems. The molecular composition of species 5 was also confirmed by high resolution mass spectrometry and we obtained a connectivity plot from an incomplete X-ray diffraction analysis (Fig S88 ).…”
Section: Synthesis Of P(iiisupporting
confidence: 81%
See 3 more Smart Citations
“…Two-electron oxidation of the P-center in 1 by reaction with an equimolar amount of p-anisylazide (4-methoxyphenylazide) also proceeded smoothly upon heating at 90 °C for several hours, cleanly forming iminophosphorane 5. This species was characterized by a 31 P NMR chemical shift of 1.8 ppm, comparable to the previously reported iminophosphoranes of PN3 (at 14.5 ppm) [39] and PN3 acr (at 18.1 ppm), [28] although it must be noted that the specific reaction conditions (temperature required and aryl azide used) distinctly vary between these three systems. The molecular composition of species 5 was also confirmed by high resolution mass spectrometry and we obtained a connectivity plot from an incomplete X-ray diffraction analysis (Fig S88 ).…”
Section: Synthesis Of P(iiisupporting
confidence: 81%
“…Equimolar reactivity of 1 with methyl triflate did lead to a single new species in the 31 P NMR spectrum at 70.2 ppm, with a 2 J P-H coupling of 16 Hz. Taken together with the new doublet at 3.06 ppm in the 1 H NMR spectrum and related data obtained by Abbenseth and Goicoechea with their version of the acridinebased PN3 acr system, [28] these data support the formation of the cationic λ 4 σ 4 -phosphorane 4 with a formal P(V) center, rather than methylation of the ligand backbone. [38] X-ray diffraction of single crystals grown from CDCl 3 -pentane corroborated this assignment (Figure 6, right) and showed that the anion is not interacting with the P(V) center in the solid state.…”
Section: Synthesis Of P(iiisupporting
confidence: 65%
See 2 more Smart Citations
“…However, among the main group elements the pnictogens stand out in this regard, often allowing access to stable species in different oxidation states, and as such they are ideal candidates for the development of metallomimetic reactivity and catalysis . A key design concept that has led to observations of redox-cycling within these systems is the introduction of geometrical constraints around the pnictogen atoms, moving them away from their preferred pyramidal to more planar geometries, resulting in changes in orbital energies and reactivity. Pincer ligands are often used for this purpose, promoting ambiphilic behavior and unusual reactivity of the pnictogen, although metal–ligand cooperativity is also frequently observed in these systems. …”
Section: Introductionmentioning
confidence: 99%